2001
DOI: 10.1097/00000542-200111000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Halothane Inhibits Contraction and Action Potential Duration to a Greater Extent in Subendocardial than Subepicardial Myocytes from the Rat Left Ventricle

Abstract: Action potential duration was reduced to a greater extent in subendocardial than subepicardial myocytes, which would contribute to the greater negative inotropic effect of halothane in the subendocardium. Furthermore, the transmural difference in action potential duration was reduced by halothane, which could contribute to its arrhythmogenic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This could increase the susceptibility of the heart to arrhythmias initially induced by premature ventricular excitation through physiological phenomena such as EADs and triggered beats or via artificial premature excitation using PES. This first report of such phenomena in the isolated, perfused whole-heart model complements one previous study in isolated endocardial and epicardial rat myocytes that suggested that a reduction in TDR might also be proarrhythmic (Rithalia et al 2001). Our results in the intact myocardium directly demonstrate that a reduced transmural gradient in APD can afford a mechanism of proarrhythmia.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This could increase the susceptibility of the heart to arrhythmias initially induced by premature ventricular excitation through physiological phenomena such as EADs and triggered beats or via artificial premature excitation using PES. This first report of such phenomena in the isolated, perfused whole-heart model complements one previous study in isolated endocardial and epicardial rat myocytes that suggested that a reduction in TDR might also be proarrhythmic (Rithalia et al 2001). Our results in the intact myocardium directly demonstrate that a reduced transmural gradient in APD can afford a mechanism of proarrhythmia.…”
Section: Discussionsupporting
confidence: 84%
“…This in turn would facilitate the generation of local conduction block and of consequent re‐entrant arrhythmogenesis (Wolk et al. 1999, Rithalia et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several volatile anesthetics have been reported to affect the APD (11)(12)(13). However, the effects have been extremely inhomogeneous.…”
Section: Basic Electrophysiology Of the Cardiomyocyte And Arrhythmiasmentioning
confidence: 99%
“…Even responses to physiologic (exercise, 14 memory 15 ), pharmacologic (drugs 16 ), and pathophysiologic stimuli (disease) vary in the endocardium versus the epicardium. In some instances, responses to drugs and disease 17 have been shown to attenuate baseline heterogeneities.…”
Section: Introductionmentioning
confidence: 99%